Development Jona Garden Destination City of Binjai (Socio-economic Analysis Approach) - Rambe, Rizki Suhanry; Yusrizal, Yusrizal; Nasution, Muhammad Lathief Ilhamy (Quantitative Economics and Management Studies, 2024)
This research aims to find out how the development of Binjai City Tourist Destinations. The research method used is descriptive with a quantitative approach. Where the data gathered through observations, interviews, and queries will be sorted as efficiently as possible to be more easily understood by the reader. The analysis used is based on SWOT analysis, i.e. by looking for strengths, weaknesses, opportunities, and threats in the development of Jona Garden Destination City of Binjai. Therefore, the strategy to be developed is the strategy and treat with the maximum possible use of tourism development in order to prosper further. The strengths that Jona Garden Binjai has to develop are the beauty of tourist objects, preserving the uniqueness of the tourist attractions, enhancing the social sense with the tribal, racial, religious, social and cultural surroundings of the objects of tourism, improving the quality of the Human Resources of the staff, promoting it either through social media or through relations with the tourism service.